Musculoskeletal Discomfort Faced by Workers in Cauliflower Production Through Traditional or Conventional Method - Reena Solanki; Manju Mehta; Anju Khichar (Archives of Current Research International, 2025)
This study was conducted with an aim to analyze the musculoskeletal discomfort faced by the workers while performing different activities through traditional/conventional method. For the field survey,30 healthy workers were selected. The musculoskeletal discomfort was evaluated through human body map, VAD scale and pain symptoms. The results revealed that out of different activities involved in cauliflower production, hands suffered the intensity of musculoskeletal discomfort with weighted mean score of 3.8 followed by thigh (3.6), neck (3.5), lower back (3.4) got rank I with mean score of 35.7 in transplantation activity. The least intensity of musculoskeletal discomfort was found in manure and fertilizers spreading activities. According to VAD scores, majority of the respondents faced highest discomfort in transplanting activity, which had a scored rank I with score of 8.2. And also indicated that pain symptom perceived rating scale by workers involved in transplanting activity got Ist rank with score of 5.1.